Semantic validation of nursing outcome dry eye severity in intensive care - Araújo, Mércio Gabriel de; Silva, Amanda Barbosa da; Dantas, Ana Clara; Araújo, Jéssica Naiara de Medeiros; Júnior, Marcos Antonio Ferreira; Vitor, Allyne Fortes (Revista de Enfermagem da UFPI, 2024)
Objective: To semantically validate the indicators of the nursing outcome Dry Eye Severity in adult patients admitted to the intensive care unit. Methods: Methodological study of semantic validation developed with 15 nurses from an adult general ICU of a public university hospital located in the Northeast of Brazil. Data collection took place between the months of February and April 2019. For data analysis, the Kappa test was used with a value equal to or greater than 85% agreement. A value of p<0.05 was used to indicate statistical significance when the proportion was less than 85%. Results: After evaluating the nurses in relation to the constitutive and operational definitions and operational magnitudes of the indicators, all presented agreement ≥ 0.85. As all indicators that presented statistically significant p values (p < 0.05) presented a cutoff point with perfect agreement, all were admitted. In addition, the nurses' comments and suggestions were taken into account for the final version of the analysis. Conclusion: In the general evaluation of the NO Dry Eye Severity by the nurses, it was...